A green ultra‐fast liquid chromatographic method for quantification of curcumin in extract of Curcuma longa L. followed by confirmation via spectroscopic techniques. Issue 3 (6th January 2021) - Ahmed, Mahmood; Ahmad, Saghir; Irfan, Masooma
Abstract: Curcumin is a principle component among the curcuminoids mixture that has diverse pharmacological properties against different phenotypes of various disease models. Present research aimed to extract (Soxhlet extractor), isolate (column chromatography), and identify (thin‐layer chromatography) the curcumin in roots and commercially available turmeric powder, and consequently its confirmation was done by spectroscopic techniques such as infrared, nuclear magnetic resonance, and mass spectrometry. Subsequently, its quantification was done by ultrafast liquid chromatography using a green analytical methodology approach. Combination of ethanol and water in a ratio of 95:5 %v/v, was used as a green mobile phase, whereas the detection was set at 425 nm at a flow rate of 0.6 mL/min. The overall run time per sample was 4.0 min with a retention time of 2.22 min, whereas calibration curve was linear from 10 to 60 μg/mL with a coefficient of determination ( R 2 ) = 0.9988. The low values of %RSD (<2%) reflect the high precision of the method. Additionally, an assessment of the greenness of the proposed method was carried out using Eco‐scale (penalty points) and national environmental methods index labeling based on a blank or green quadrant of pictogram. The proposed liquid chromatography method showed priority over the reported methods in terms of greenness having Eco‐scale value of 93 and passed the four quadrants of greenness profile.